2017
DOI: 10.2147/copd.s129787
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood eosinophils, clinical characteristics, and mortality in patients with COPD

Abstract: In patients with COPD, there is controversy regarding the association of blood eosinophil (Eos) levels with 1) exacerbation frequency and 2) the effect of inhaled corticosteroids for prevention of exacerbations. To determine whether Eos define subgroups of patients exhibiting attributes of COPD clinical phenotypes, we compared clinical features and mortality rates in COPD patients from the Initiatives BPCO French cohort categorized using different thresholds of blood Eos levels. The following data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 17 publications
6
58
0
3
Order By: Relevance
“…Furthermore, in the CHAIN and BODE cohorts, the prevalence of ICS use was similar in patients with persistently high, intermittently variable or persistently low eosinophil counts (supplementary table S2), thus negating an effect of use of ICSs on the findings reported here. The lack of a relationship between eosinophil level and outcomes is similar to the results reported by ZYSMAN et al [29], who followed 458 patients with COPD for an average of 3 years. They observed no difference in exacerbation rates of asthma or COPD exacerbations irrespective of the threshold of eosinophils used for the analysis.…”
Section: Eosinophils and Outcomes In Copdsupporting
confidence: 88%
“…Furthermore, in the CHAIN and BODE cohorts, the prevalence of ICS use was similar in patients with persistently high, intermittently variable or persistently low eosinophil counts (supplementary table S2), thus negating an effect of use of ICSs on the findings reported here. The lack of a relationship between eosinophil level and outcomes is similar to the results reported by ZYSMAN et al [29], who followed 458 patients with COPD for an average of 3 years. They observed no difference in exacerbation rates of asthma or COPD exacerbations irrespective of the threshold of eosinophils used for the analysis.…”
Section: Eosinophils and Outcomes In Copdsupporting
confidence: 88%
“…More recently, the Copenhagen City Lung study strongly suggested that a high peripheral blood eosinophil count (>340 cells per µL) was associated with an increased risk of severe COPD exacerbations [5]. In contrast, and similar to the results of the ECLIPSE study [6] and of ZYSMAN et al [7], both of which were conducted in patients with COPD, no increased risk of moderate-severe exacerbations was found when a threshold of 2% blood eosinophils was used [5]. Finally, contributing to the overall confusion about the role of eosinophils as a risk factor for COPD outcomes, increased blood eosinophils in patients with COPD were also associated with better lung function, improved quality of life [6,8], and even reduced mortality [9].…”
mentioning
confidence: 53%
“…6 Another study that had assessed the peripheral eosinophil count of a French cohort (not during exacerbations) found no significant difference in mortality between COPD patients with higher versus lower blood eosinophil levels, for all tested thresholds of eosinophils (2%, 3% and 4%) with a median follow-up period of 48 months. 23 A spot peripheral eosinophil count on hospitalization probably could only have some prognostic use for that particular exacerbation but not on longer term outcome. FEV 1 appeared to have mild improvement for those with higher eosinophil cut-off value.…”
Section: Discussionmentioning
confidence: 99%